Correction: Late-season surveys to document seed rain potential of Palmer amaranth (Amaranthus palmeri) and waterhemp (Amaranthus tuberculatus) in Texas cotton. - PLOS ONE Staff (PLoS ONE, 2021)
[This corrects the article DOI: 10.1371/journal.pone.0226054.].